Factors associated with non-adherence to highly active antiretroviral treatment in HIV/AIDS patients - Alvis, Óscar (2009)
Introduction: Non-adherence to highly active antiretroviral treatment (HAART) is the principal reason of therapeutic failure. Objectives: To determine the prevalence and factors associated with non-adherence to HAART in HIV/AIDS patients. Design: Cross-sectional study. Setting: Infectious diseases service, Arzobispo Loayza National Hospital, a teaching hospital. Participants: HIV-infected patients on treatment with highly active antiretroviral treatment. Interventions: HIV-infected patients on treatment with highly active antiretroviral treatment were invited to complete a constructed questionnaire based on instruments evaluating adherence and associated factors. x2-test and Student’s t test were used to determine association; p-values below 0,05 were considered significant. Association magnitude was measured by OR and 95% confidence intervals. A multivariate logistic regression analysis was performed. Main outcome measures: Non-adherence to highly active antiretroviral treatment. Results: Four hundred and sixty five patients were interviewed, median age 36,8±9,1 years, 64,1% males. Nearly 35,9% of the sample was considered non-adherent. In multivariate analysis, being homosexual/bisexual (OR 3,85, 95%CI 1,98-7,51), having a low health-related quality of life (OR 6,22, 95%CI 3,47-11,13), low social support (OR 5,41, 95%CI 3,17-9,22), not having a permanent residence (OR 3,34, 95%CI 1,93-5,79), having psychological morbidity (OR 2,93, 95%CI 1,78-4,82) and having received treatment for a long time (OR 1,04, 95%CI 1,02-1,07) were independently associated with non-adherence. Conclusions: The prevalence of non-adherence was higher than the previously reported in this hospital, but similar to many studies despite their heterogeneity. Mainly psychosocial factors influenced non-adherence to antiretroviral treatment.